2018
DOI: 10.1136/emermed-2018-207485
|View full text |Cite
|
Sign up to set email alerts
|

Achieving just outcomes: forensic evidence collection in emergency department sexual assault cases

Abstract: Even with access to specialised forensic evidence collection, many sexual assault survivors do not complete a SAEK, and even fewer release the evidence to police for investigation. The ED is a common entry points into the healthcare system, and this study has highlighted the need to strengthen services and reduce attrition along the health-justice continuum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…In previous studies, we have identified that approximately two thirds of eligible case complete a Sexual Assault Evidence Kit, and one third release it to police [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, we have identified that approximately two thirds of eligible case complete a Sexual Assault Evidence Kit, and one third release it to police [34].…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted in Ottawa, Ontario, the fourth largest city in Canada with a census metropolitan population of 1.3 million. At the time of the study, there were 2650 COVID- 19 [34]; crisis counseling; and risk/threat assessment and safety planning. There were no reductions or changes to program staffing, procedures, or services since the COVID-19 pandemic began, except for an increase in personal protective equipment (e.g., universal masking) as part of the hospital-wide policy.…”
Section: Study Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who are below 16 years of age are transferred to the pediatric sexual assault clinic at the Children's Hospital of Eastern Ontario. The SAPACP is the only facility in the region that administers the Sexual Assault Evidence Kit (SAEK, also known as the "rape kit") and is a main point of care to transition from the health care system into the legal system to pursue prosecution (Muldoon, Drumm, Leach, Heimerl, & Sampsel, 2018). The SAPACP works closely with several community-based programs including Ottawa Victim Services and the Ottawa Rape Crisis Center to ensure that survivors are supported following their encounter with the hospital.…”
Section: Settingmentioning
confidence: 99%
“…As described in the EMJ paper by Muldoon and colleagues, the collection of forensic evidence by specially trained clinicians may increase the effectiveness of legal prosecution, and is often assumed to be a ‘just’ or, in other words, desired outcome 2. The decision to obtain, and then process, forensic evidence, however, must be an individual, personal decision made by each and every survivor, informed by their own priorities, values and needs, and supported non-judgementally by emergency healthcare providers acting in a trauma-informed manner.…”
mentioning
confidence: 99%